THE ROLE OF HEALTH CENTERS ON OCCUPATIONAL SAFETY OF HEALTH PERSONNEL DUE TO THE COVID-19 PANDEMIC - Partini Partini; Anggraeni Endah Kusumaningrum (UNTAG Law Review, 2021)
The function of the Puskesmas is as a First Level health service in carrying out health service efforts, both promotive, preventive, curative, and rehabilitative in its working area. During the Covid-19 pandemic, Puskesmas are expected to provide services according to the Covid-19 situation. The goal is that the implementation of health protocols in health service facilities in order to prevent and control Covid-19 is carried out as well as possible. Puskesmas as a place used to carry out health service efforts has the potential to spread infectious diseases, including covid -19. Sources of infection transmission can come from the community or community or from the health care facilities themselves. The application of standard precautions in Infection Control and Prevention is not optimal. as a result, many health center health workers were confirmed covid-19. The purpose of this research is the extent to which the Puskesmas efforts in providing legal protection for the safety of health workers due to the Covid -19 pandemic. Legal protection for the work safety of health workers must be carried out as well as possible so that the rights of health workers to life safety are fulfilled. This research method is juridical sociology where this research is built from social facts related to the operation of real laws faced in health facilities or in the community. The problem faced in puskesmas is their adherence to health protocols is weak and tends to ignore. Second, Puskesmas is less obedient to infection prevention and control. There are many risk factors that arise in the Puskesmas environment such as unsterile medical equipment, unavailability of infectious and non-infectious trash bins in the work room, and the absence of adequate medical waste management. Third, the density of the puskesmas program activities causes the risk of being exposed to Covid-19 even higher. Based on the above background, the researchers took the title of the role of the Puskesmas in the safety of health workers due to the Covid-19 pandemic.